Evaluation of management of angle fracture of mandible by using different surgical approaches - Mahat, Arun Kumar; Shrestha, Merina; Chaudhary, Bishwanath (Birat Journal of Health Sciences, 2020)
Introduction: Mandible is frequently involved bone in facial fracture with angle fracture accounting for 27-30% of cases. Various methods and approaches have been tried for treatment of angle fracture. Objective: To correlate the different surgical approaches with its outcome postoperatively Methodology: A hospital based descriptive observational study was conducted in 30 patients admitted in DentalInpatient Department (IPD), from October 2016 to April 2019. ASA Ipatients having angle fracture of mandible either isolated or combined with other facial bones were included in the study. Different approaches were used for management of angle fracture of mandible. Patient characteristics were presented using frequency table and percentages. Result: The mean operative duration was lesser in transbuccal approach (111.25 minutes) compared to transbuccal (lower border) approach (120 minutes) and intraoral (122.5 minutes) in case of isolated angle fracture. Ease of surgical access was good in transbuccal approach 7 patients (70%) compared to intraoral approach 6 patients (42.86%). Occlusal discrepancies were more in transbuccal approach (50%) compared to intraoral approach (21.43%). Scar was barely visible in 2 patients (14.29%) out of 14 patients wheretransbuccal incision was made. Conclusion: We recommend intraoral surgical approach for favorable angle fracture. In unfavorable fractures we advise to place the first miniplate via intraoral approach, check for fracture stability intra-operatively and place second miniplate on lower bordervia transbuccal approach if unstable.